Manejo alimentar e retorno econômico de tilápia do Nilo (Oreochromisniloticus) cultivada em tanques-rede, no período de inverno - Tardivo, Thiago Fontolan (2011)
This study aimed to evaluate the performance and economic viability of farming Nile tilapia (Oreochromis niloticus) in cages in the winter in the Corvo River, Paraná - Brazil. The research involved the evaluation of biological indices, economic return and investment analysis of three feeding strategies in the winter season of animals. The species used was the Nile tilapia, Oreochromis niloticus GIFT strain, sexually reversed. 12,600 juveniles were used with average weight of 45 grams, divided into cages of useful 6.0 m³ . The experimental period was 180 days. Extruded feed was used with 35% CP (4mm) and / or 30% CP (4mm and 6mm), used according to the weights and the management adopted. In the first food management (FM1) was feed 30% CP (4 and 6mm). In the second feed management (FM2) was used a diet with 35% CP (4 mm) to 150 to 200 grams and a diet with 30% CP (6mm) to the end of fattening. In the third feed management (FM3) with 35% CP diet (4mm) to 350 to 400 grams and diet with 30% CP (6mm) to the end of fattening. Samples were collected monthly to monitor consumption. For performance evaluation data were applied analysis of variance by GLM procedure, followed by multiple comparison of mean adopting the Tukey test (p <0.05). The average water temperature of the experimental period was 22.0 ° C below the comfort zone of the species. The cost structure of production used was developed considering the methodology of Production and Operating Cost and profitability indicators of Gross Revenue, Operating Income, and Gross Point Leveling. From the preparation of cash flow for 60 months were obtained the following indicators: Internal Rate of Return, Net Present Value, Benefit-Cost and Capital Recovery Period. The discount rate used was 0.07% per month. Analyzing the production performance of the period, there was no difference (p <0.05) between feeding strategies for the final weight, weight gain, daily weight gain, feed conversion and productivity. Survival rates were different (p <0.05) between feeding strategies, with the best results for FM1 (88.90%). The total consumption of food also differed (p <0.05) between the managements. The high feed conversion influenced by treatments influenced the Operating Costs Effective leading to a higher total production costs. The lowest total operating cost was found in the FM1 (R$2,66). Operating income per pound of fish produced was similar to the FM1 and FM2 (R$0,07 / kg fish). The loss FM3 obtained at the end of the cycle (R$ 0,05). The internal rates of return obtained by feeding strategies 1 and 2 (1.051 and 1.044%) were above the pay rates of savings. The FM1 proved to be the best option in the winter.